A case study of trainee teachers' mental models of history teaching before and after an initial history teaching professional development course. (26th October 2018) - Oppong, Charles Adabo
The study compares 28 third-year University of Cape Coast trainee teachers' perceptions and mental models of history teaching before and after an initial history teaching professional development course – the Methods of Teaching History Course – to prepare them to teach history. The History Course was an intervention strategy built around episodic memory theory. The research questions were: Do trainees' perceptions (mental models) of history teaching remain the same or change during the History Course? If they change, how and why? Research involved all 28 trainees before and after they took the course through the use of a questionnaire and vignettes, plus a post-course interview of 12 of the trainees. The researcher used a deductive approach to analyse data about three aspects of the trainees' history teaching mental models: pedagogy, teaching styles as illustrated through classroom organization, and how students learn history. Findings revealed a marked difference between the trainees' pre- and post-course mental models of what school history is and how it should be taught. The trainees' pre-course mental models changed as a result of the knowledge and understanding they acquired during the History Course. A major finding was that such professional development courses need fully to take account of trainees' pre-course conceptions that shape their mental models of history teaching.